CHILDFREE IN THE PERSPECTIVE OF ISLAMIC LAW (CHILDFREE DALAM PERSPEKTIF HUKUM ISLAM) - Dita Dita; Takdir Takdir; Rahmawati Rahmawati (Universitas Labuhanbatu, 2024)
This research analyzes the perspectives of married couples on childfree choices, explores the factors influencing the decision to be childfree, and investigates the Islamic perspective on this matter. Employing a literature review method with a normative approach, the study references Islamic legal norms through primary sources such as journals, articles, and books related to childfree. The findings indicate that the decision to be childfree is typically a joint one made by spouses. Women often express a desire for childfree living, feeling burdened by pregnancy, and believing that without children, they can maintain a youthful appearance and focus on their careers without the responsibilities of parenthood. Economic, mental, cultural, environmental, and concerns about overpopulation are identified as primary reasons behind this decision. From an Islamic perspective, although there is no direct prohibition in the Quran regarding childfree choices, the decision is considered contrary to the marital goal of procreation. Consequently, within the religious context, intentionally childless couples are deemed to violate the principles of marriage in Islam. This research provides insights into the dynamics of childfree decisions among married couples, encompassing economic, psychological, and cultural aspects, while highlighting the religious perspective that influences attitudes toward childfree choices.Keywords: Childfree, Marriage, Islamic Law.